Lanostane Triterpenoid Metabolites from a Penares sp. Marine Sponge Protect Neuro-2a Cells against Paraquat Neurotoxicity - Yurchenko, Ekaterina A. (Molecules, 2020)
The results of an investigation of the protective effects of five lanostane triterpenoids: 3β-acetoxy-7β,8β-epoxy-5α-lanost-24-en-30,9α-olide (1), 3β-hydroxy-7β,8β-epoxy-5α-lanost-24-en- 30,9α-olide (2), 29-nor-penasterone (3), penasterone (4), and acetylpenasterol (5), from a marine sponge, Penares sp., against paraquat-induced neuroblastoma Neuro-2a cell damage, are described. The influence of all compounds on viability of the Neuro-2a cells treated with paraquat (PQ) was studied with MTT and fluorescein diacetate assays as well as propidium iodide straining. 1,1-Diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity of the compounds as well as their influence on reactive oxygen species (ROS) level and mitochondrial membrane potential in PQ-treated neuronal cells were analyzed. Finally, the effect of the compounds on intracellular level of heat shock protein 70 kDa (Hsp70) and neurite outgrowth in PQ-treated Neuro-2a cells were studied. Studied triterpenoids demonstrated protective effects against PQ-induced neurotoxicity associated with the ability to reduce ROS intracellular level and diminish mitochondrial dysfunction. Acetylpenasterol (5), as a more promising neuroprotective compound, significantly increased the viability of Neuro-2a cells incubated with PQ as well as decreased intracellular ROS level in these cells. Moreover, acetylpenasterol induced Hsp70 expression in PQ-treated cells. It was also shown to inhibit PQ-induced neurite loss and recovered the number of neurite-bearing cells. The relationship between neuroprotective activity of the investigated compounds 1–5 and their chemical structure was also discussed.